2013
DOI: 10.1007/s00246-013-0794-1
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Doppler Septal Tei Index Indicates Severity of Illness in Pediatric Patients With Congestive Heart Failure

Abstract: Background: The Doppler Tei index is an independent predictor of outcomes in adult heart failure. Tissue Doppler imaging (TDI) may be a superior method to measure the Tei index in children, as it is less affected by heart rate variability. We hypothesized that the TDI Tei index reflects severity of illness in pediatric heart failure. Methods: Twenty-five pediatric heart failure patients were prospectively enrolled. Listing for heart transplantation or death were the outcomes used to define severity of illnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
(46 reference statements)
2
7
0
Order By: Relevance
“…From the findings of the present study, children with CHF had reduced cardiac function parameters detected by TDI that included reduced left ventricular ejection fraction (LVEF), left ventricular fractional shortening (LVFS), and ejection time (ET), and increased MPI TDI and MPI TDI-R. The findings in children with CHF probably affected both ventricular systolic and diastolic dysfunction as has been previously shown [ 15 ]. In this study, receiver-operating characteristic (ROC) curve analysis showed that the MPI TDI-R had a sensitivity of 67.5%, and a specificity of 97.5%, which was better than for MPI TDI.…”
Section: Discussionsupporting
confidence: 80%
“…From the findings of the present study, children with CHF had reduced cardiac function parameters detected by TDI that included reduced left ventricular ejection fraction (LVEF), left ventricular fractional shortening (LVFS), and ejection time (ET), and increased MPI TDI and MPI TDI-R. The findings in children with CHF probably affected both ventricular systolic and diastolic dysfunction as has been previously shown [ 15 ]. In this study, receiver-operating characteristic (ROC) curve analysis showed that the MPI TDI-R had a sensitivity of 67.5%, and a specificity of 97.5%, which was better than for MPI TDI.…”
Section: Discussionsupporting
confidence: 80%
“…In these severe categories of bronchial asthma, conventional echocardiography started to detect left ventricular diastolic dimension and right ventricular systolic pressure changes. In a study done by Sanchez Mejia et al, TDI of the septal Tei index was found to be a more sensitive indicator of the disease severity than the TDI free wall Tei index. The enhanced sensitivity of the septal Tei index may reflect the combined dysfunction of the left and right ventricles.…”
Section: Discussionmentioning
confidence: 92%
“…The Tei index combines the systolic and diastolic functions of ventricles in an index of global myocardial performance. 14) It correlates with the severity and clinical outcome in children with cardiac disease. 14) 28) The Tei index could be used as an accurate tool for estimating myocardial function in KD patients.…”
Section: Discussionmentioning
confidence: 99%
“… 14) It correlates with the severity and clinical outcome in children with cardiac disease. 14) 28) The Tei index could be used as an accurate tool for estimating myocardial function in KD patients. 29) According to Ajami et al 30) after IVIG treatment in KD patients, the Tei index changed from 0.43±0.08 to 0.35±0.06.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation